Assessment of traffic inputs to pavement design and rehabilitation - Regidor, Jose Regin F.; Damaso, Romeo A. II.; Bilugan, April Rose V.
Traffic and the consequent loads that vehicles transfer to the roads are major factors considered in pavement design. Heavy vehicles, particularly trucks that carry the largest loads cause the most damage to pavements. In the design process, axle loads attributed to heavy vehicles are derived and the total equivalent standard loads are estimated over a design period. The total loads are then utilized in coming up with the appropriate design that takes into account pavement type and thickness, among others. This paper analyzes the traffic inputs to pavement design through assessment of actual highway sections along the Pan-Philippine Highway also known as the Doa Remedios Trinidad Highway. Original design loads due to previous projections of traffic is compared to present loads and new projections of future traffic loads. As such, pavement performance level could be gauged and the adequacy of current pavement types and thickness can be determined. Recommendations are formulated and proposed in relation to the importance of accurate traffic inputs in pavement design, especially the development of heavy vehicle factors that allow for a more accurate estimation of equivalent axle loads as well as implications to economic design of pavements.
Keywords: Traffic inputs; Axle loads; Pavement design